Examination of the relationship between school principals' democratic leadership behaviors and diversity management skills - ÇAYAK, SEMİH (My University, 2023)
The aim of this study is to examine the relationship between school principals' democratic leadership behaviors and their ability to diversity management according to teacher perceptions. This study was designed using a correlational survey model. Sample of the research consists of 307 teachers working in Pendik and Kartal districts of Istanbul. “Democratic Leadership Scale” and “Diversity Management Scale” were used in the research. Research data were analyzed using arithmetic mean, standard deviation, correlation analysis, and regression analysis. According to the findings, the democratic leadership behaviors of school principals were at a moderate level, and their diversity management skills were at a low level. The results of the correlation analysis showed that there was a positive, low-level, significant relationship between the two variables. Finally, as a result of the simple linear regression analysis, it was found that school principals' democratic leadership behaviors were a significant predictor of their diversity management skills. The findings obtained from the research were discussed in line with the relevant literature and some suggestions were presented for researchers and practitioners.
Keywords: Democratic Leadership; Diversity Management; School Principals